pyObs: Open-Source Software for Computer-Assisted Behavioral Observation Coding - Griffin, William A. (Journal of open research software, 2018)
pyObs is a computer-assisted behavioral observation coding system used to record social interaction among children in classroom and playground settings. Its flexible architecture allows it to be useful for capturing behaviors occurring in settings that vary across age group or context. Written in Python, pyObs has a cross-platform GUI using drop down menus and check boxes along with audio and visual cues that increase coder reliability. Time-stamped GIS maps record subject location. And data are output into standard formats, such as csv. pyObs is extensible, making it simple to change the interface depending on the research objectives.Keywords: observational coding, behavior, ethology, classroom, playground, children, autism, Python, wxPython